Bibliometric analysis on the international publication of muslim brotherhood - Iqbal Rasyad; Gonda Yumitro (Communications in Humanities and Social Sciences, 2023)
This article analyzes the trend of international publications related to the Muslim Brotherhood using the Scopus database. This study aims to determine the publication trends by region, subject area of publication, type of publication, number of documents for each author, and number of papers for each university. The data collected by the authors were taken from the search results in the Scopus database with a combination of the keywords "Ikhwanul Muslimin or Muslim Brotherhood" with the categories of article titles, article abstracts, and article keywords in the publication period of 1954 - 2023. Based on this search, the authors found 738 scientific publication documents related to the Muslim Brotherhood. The studies conducted in 2023 were 17 publications, and the highest number found by the authors was 69 scientific publications (9.3%) in 2016. The United States became the most productive country or region in scientific publications with 175 papers (23.7%). The most prolific authors are Ardovini and Brooke with eight articles. Bar-Ilan University became the affiliate with the most publications with 15 publications. Based on these results, the study of the Muslim Brotherhood became a contemporary study that has attracted the interest of researchers.